2018
DOI: 10.3390/ma11081484
|View full text |Cite
|
Sign up to set email alerts
|

Some Considerations about the Use of Contact and Confocal Microscopy Methods in Surface Texture Measurement

Abstract: Surface metrology employs various measurement techniques, among which there has been an increase of noteworthy research into non-contact optical and contact stylus methods. However, some deeper considerations about their differentiation and compatibility are still lacking and necessary. This work compares the measurement characteristics of the confocal microscope with the portable stylus profilometer instrumentation, from a metrological point of view (measurement precision and accuracy, and complexity of algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…This evaluation method has been used in dentistry, for dentin and enamel evaluating. Optical methods are useful in dentistry [46,47]. Finally, a 2010 RCT by Mohire and Yadav [21] was an interesting study that evaluated chitosan-based polyherbal toothpaste properties and reported that this toothpaste was a promising product as compared to standard oral hygiene products.…”
Section: Discussionmentioning
confidence: 99%
“…This evaluation method has been used in dentistry, for dentin and enamel evaluating. Optical methods are useful in dentistry [46,47]. Finally, a 2010 RCT by Mohire and Yadav [21] was an interesting study that evaluated chitosan-based polyherbal toothpaste properties and reported that this toothpaste was a promising product as compared to standard oral hygiene products.…”
Section: Discussionmentioning
confidence: 99%
“…The light beam direction mechanism is managed by computerized systems. The images obtained, by synchronizing the detection device with the excitation beam, are particularly defined and spectacular, and can allow the different molecules present in the preparation to be highlighted in different colors, making it possible to appreciate their three-dimensionality [53,54] (Figure 4, Figure 5, Figure 6 and Figure 7).…”
Section: Methodsmentioning
confidence: 99%
“…With the introduction of areal surface texture parameters in the scientific and industrial field [26,27], commercial software packages have been developed in parallel with their calculation, such as those implemented by the National Physical Laboratory (NPL) [28], and the use of optical instruments for the implementation of these measures has increased [29,30,31,32], with confocal microscopes being one of the most used instruments.…”
Section: Introductionmentioning
confidence: 99%